Editorial - Pawlak, Mirosław (Studies in Second Language Learning and Teaching, 2013)
The present issue of Studies in Second Language Learning and Teaching marks exactly three years of existence of the journal. On the one hand, this has not been a very easy time, mainly because of the fact that, as is the case with any startup publication, it has been extremely difficult to obtain papers that would satisfy the stringent criteria of high-quality academic research, with the effect that the rejection rate has been extremely high, and finding the right reviewers has also often constituted a major challenge. On the other hand, the three years have also witnessed the rise of SSLLT in the field, as we have been privileged to publish papers by prominent scholars in the area of second language acquisition, well-known researchers have consented to act in the capacity of editors of special issues of the journal, and eminent figures have also agreed to review many of the submissions we have received. Equally importantly, there has been increasing interest in the papers we publish, which is evidenced in the growing numbers of downloads and citations, a clear advantage of having both a printed and an online version, the latter of which is accessible to everyone free of charge. I would like to take this opportunity to thank all those who have been involved in the production of the journal over these three years and have spent countless hours to make sure that the final product is each time up to standard. In particular, my sincere thanks go to assistants to the editor Anna Mystkowska-Wiertelak, Jakub Bielak, Mariusz Kruk and Krzysztof Kwiatkowski, our typesetter Piotr Bajak, as well as the authors and anonymous reviewers. Had it not been for their attention to detail, dedication, hard work and support, SSLLT would surely not have gained the position in the field it enjoys today.